2017
DOI: 10.1016/j.jviromet.2017.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Sampling methods for recovery of human enteric viruses from environmental surfaces

Abstract: Acute gastroenteritis causes the second highest infectious disease burden worldwide. Human enteric viruses have been identified as leading causative agents of acute gastroenteritis as well as foodborne illnesses in the U.S. and are generally transmitted by fecal-oral contamination. There is growing evidence of transmission occurring via contaminated fomite including food contact surfaces. Additionally, human enteric viruses have been shown to remain infectious on fomites over prolonged periods of time. To bett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 43 publications
(106 reference statements)
1
13
0
Order By: Relevance
“…However, studies have shown that other sampling tools such as bio wipes and cell scraper-aspiration methods could be more efficient than swabs to recover viruses from surfaces due to higher moisture retention ( De Keuckelaere et al, 2014 ; Taku et al, 2002 ). A review study concluded that more techniques and tools of recovery of viruses from environmental surfaces need to be evaluated and these evaluations should include a variety of human viruses ( Turnage and Gibson, 2017 ). Most studies reported results as either positive or negative or with Ct values, while some gave the viral concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have shown that other sampling tools such as bio wipes and cell scraper-aspiration methods could be more efficient than swabs to recover viruses from surfaces due to higher moisture retention ( De Keuckelaere et al, 2014 ; Taku et al, 2002 ). A review study concluded that more techniques and tools of recovery of viruses from environmental surfaces need to be evaluated and these evaluations should include a variety of human viruses ( Turnage and Gibson, 2017 ). Most studies reported results as either positive or negative or with Ct values, while some gave the viral concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Many factors of an elution mixture can impact the elution efficiency of viruses from materials, including difference in pH, salinity, or the use of a surfactant. 39 Tween®20 is a nonionic polysorbate surfactant widely used in biochemical applications and is known for being a gentle surfactant at lower concentrations to prevent premature cell lysis. 40 In other work, Tween®20 has been successfully implemented for ultrafiltration techniques, significantly increasing microbial recovery efficiencies.…”
Section: Comparison Of Three Elution Techniques In the Analysis Of Sars-cov-2mentioning
confidence: 99%
“…[2][3][4][5] Pathogenic microbes may be transmitted directly from person-to-person or indirectly via contamination of surfaces leading to both healthcare-acquired infections (HAIs) and community-acquired infections (CAIs). [6][7][8] The exact mechanism of microbial death from copper is controversial and the significance and relative contribution of each proposed mechanism are unclear. One method is the physical interaction of the CuNPs with the cell, or virus, plasma membrane leading to its destruction, making the microbe susceptible to damage from copper ions.…”
Section: Introductionmentioning
confidence: 99%